2001
DOI: 10.1063/1.1385190
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of aerosol silicon nanocrystal nonvolatile floating-gate memory devices

Abstract: This letter describes the fabrication and structural and electrical characterization of an aerosol-nanocrystal-based floating-gate field-effect-transistor nonvolatile memory. Aerosol nanocrystal nonvolatile memory devices demonstrate program/erase characteristics comparable to conventional stacked-gate nonvolatile memory devices. Aerosol nanocrystal devices with 0.2 m channel lengths exhibit large threshold voltage shifts (Ͼ3 V), submicrosecond program times, millisecond erase times, excellent endurance ͑Ͼ10 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(83 citation statements)
references
References 6 publications
0
83
0
Order By: Relevance
“…For that aim, NCs have been synthesized by a variety of techniques like chemical vapor deposition [2], ion implantation [3,4], and Si aerosol deposition [5]. Ion implantation followed by thermally activated precipitation of the implanted impurity atoms is most compatible with current silicon technology.…”
mentioning
confidence: 99%
“…For that aim, NCs have been synthesized by a variety of techniques like chemical vapor deposition [2], ion implantation [3,4], and Si aerosol deposition [5]. Ion implantation followed by thermally activated precipitation of the implanted impurity atoms is most compatible with current silicon technology.…”
mentioning
confidence: 99%
“…To fully exploit their potential advantages over conventional floating gate memory, it is essential to control as accurately as possible Si nanocrystal size, depth distribution, and areal density, as well as nanocrystal surface passivation and oxide defect density in SiO 2 matrix, all in a process compatible with ultra-large-scale integration. Transmission electron microscopy ͑TEM͒ is the most widely used tool to characterize nanocrystal size and distribution with high resolution, [2][3][4] and sometimes electron diffraction is used to further substantiate the existence of crystallites. We have used a combination of contact-mode atomic force microscopy ͑AFM͒ and reflection high energy electron diffraction ͑RHEED͒ to identify the existence of nanocrystals, and used an ultrahigh vacuum scanning tunneling microscope ͑UHV STM͒ to estimate nanocrystal size and areal density.…”
mentioning
confidence: 99%
“…A nanocrystal free SiO 2 interface oxide (3) and oxide close to the surface devoid of Ge nanocrystal formation, (4) is observed. Ge diffuses into Si substrate for an average thickness of 50 nm, (5). Si substrate (6) and the electron damage during EDX study (7) is also indicated composed of small nanocrystals that have an average size of 15 nm and a second group of large crystals that have an average size of 50 nm.…”
Section: Resultsmentioning
confidence: 99%
“…As charge loss through lateral paths in nanocrystal based memory devices are suppressed by the oxide isolation between nanocrystals, these devices exhibit superior charge retention characteristics compared with conventional floating-gate memory devices [1][2][3][4][5]. Recently, Choi et al demonstrated the existence of memory effect in rf sputtered Ge nanocrystal devices [6].…”
Section: Introductionmentioning
confidence: 99%